Decision Model Research on Engineering Project Arrangement of Power Grid Enterprise Group Based on Input and Output Efficiency Evaluation - Lu Gang; Luan Hao; He Wan; Ma Yungao (MATEC Web of Conferences, 2015)
The engineering project arrangement of a large-scale Power Grid Enterprise Group confronts optimization problems on how to achieve efficient investment, how to achieve overall balance. This paper presents a general analytical framework, and establishes appropriate quantitative analysis models from the development of general control scale, input and output efficiency evaluation, index optimization of engineering project input of a single subsidiary, and balance optimization of engineering project arrangement of subordinate units of the Group, and so on. Simulated calculation examples show that this method is more practical, which can flexibly solve such problems.